An Overview of the Downdraft Rice Husk Gasifier Technology for Thermal and Power Applications - Belonio, Alexis T.; Ramos, Joel A.; Regalado, Manuel Jose C.; Ocon, Victoriano B. (Journal of Technology Innovations in Renewable Energy, 2013)
An overview of the downdraft rice husk gasifier (DDRHG) for thermal and power applications is herein presented. The different designs of the downdraft rice husk gasifier with reactor diameter ranging from 0.10 meter to 1.20 meter are discussed in detail. Smaller units of the DDRHG were found to have performed well in fixed bed. Larger units of the gasifier, on the other hand, are suited for moving-bed type making possible continuous operation without discharging and recharging the reactor. Present thermal applications of the gasifier includes: domestic cookstove, bakery oven, dryers, rotary kiln, steam boiler, and torrefyer. The DDRHG is also used to run surplus gasoline engines for driving water pump, micro-mill, and electric generator without any modification. The advantages and limitations of the gasifier as well as its environmental and socio-economic benefits over the use of conventional fossil-fueled systems are enumerated. At present, the investment cost for the gasifier ranges from PHP2,000 to 2,500.00 (USD 1 = PHP40.00) per kWt for thermal application and PHP20,000.00 to 30,000 per kWe for power generation. The cost of using the gasifier is much cheaper than that of the conventional fossil fuel and the investment can be recovered in a shorter period.